Comparing critical and normal match episodes in different competitive contexts of the basketball game - Ferreira, A. P.; Didier, S.; Volossovitch, A. (World Congress of Performance Analysis of Sport IX, 2012)
Few studies have been focused on the teams¡¦ strategy used in the Critical Match Episodes (CME) in different competitive contexts. This study aimed to compare the CME with the Normal Match Episodes (NME) in basketball games according to the match equilibrium and the teams¡¦ success. The current score of 80 matches from the Basketball Portuguese League were reconstructed by ball possession. Each match was analyzed according to the model of coach¡¦s game practical knowledge (Ferreira et al., 2010). A CME was considered as a transition of the equilibrium state of match score. A NME was defined as an episode in which the current score remained in the same equilibrium state. A total of 319 CME and 318 NME were analyzed. The NME were randomly selected according to a homogeneity criterion with the CME identified in each match. Offensive performance during the CME and NME were registered using an instrument that included six categories: (1) Duration of Ball Possession (DBP), (2) Offensive Phase (OP), (3) Tactical Combination (TC), (4) Field Goals Type/Zone (FG); (5) Offensive Preparation and (6) the End of Ball Possession (EBP). A total of 2665 ball possessions from CME and 2671 from NME have been observed using the referred instrument. Intra and inter-observer ratings were estimated by K-Cohen test and equaled 0,78-0,85. Matches were classified according to the match final score: balanced matches with the final point difference less than 10 points; and unbalanced matches with the final point difference equal or higher than 10 points. The team¡¦s success was defined in function of the match outcome - winning and losing teams. CME and NME of winning and losing teams in balanced and unbalanced matches were compared using the Chi test. P-value was set at 0.05 and the adjusted standardized residuals were analyzed taking account in the |1.96| boundaries. CME and NME were distinguished by DPB (Chi2 (3, n=956) = 14.001, </= . 0.01) in balanced and unbalanced matches. In addition, balanced matches showed differences in FG (Chi (10, n=1508) = 23.625,</=. 0.01). CME of winning teams presented significant differences in more features: DBP (Chi2 (3, n=1283) = 17.662, £l. 0.01), OP (£q2 (2, n=1283) = 7.902, £l. 0.01), TC (Chi2 (4, n=1283) = 13.474, </=. 0.01), FG (Chi2 (10, n=1283) = 47.756, </=. 0.01) and EBP (Chi2 (12, n=1283) = 23.011, </=. 0.05). Losing teams demonstrated located differences in DBP (Chi2 (3, n=124) = 14.676, </=. 0.001) and in OP (Chi2 (2, n=1254) = 6.857, </=. 0.01). Regarding the contextual factors the CME showed clear differences in the ball possessions with duration between 9 and 12 seconds. It could mean that in basketball game teams tend to provoke CME when the secondary fast break forms are predominant in the offensive play in detriment of the positional forms of attack.